2017
DOI: 10.4155/fsoa-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Catabolic and Anabolic Faces of Insulin Resistance and their Disorders: A New Insight into Circadian Control of Metabolic Disorders Leading to Diabetes

Abstract: Maintenance of glucose homeostasis during circadian behavioral cycles is critical. The processes controlling the switch between predominant lipolysis/fatty oxidation during fasting and predominant lipid storage/glucose oxidation following feeding are determined principally by insulin. Chronic elevated threshold of insulin resistance (IR) is a key pathological feature of obesity, Type 2 diabetes, sepsis and cancer cachexia; however, a temporal reduced threshold of IR is widely met in fasting/hibernation, pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Because of similar exercise induced drops in insulin levels in all groups, changes in body composition could be considered as another factor taking part in different exercise induced adaptations between athletic and obesity phenotypes. These results suggest that individuals with obesity phenotype are more susceptible to insulin resistance, what has been confirmed in obese individuals (28).…”
Section: Discussionsupporting
confidence: 65%
“…Because of similar exercise induced drops in insulin levels in all groups, changes in body composition could be considered as another factor taking part in different exercise induced adaptations between athletic and obesity phenotypes. These results suggest that individuals with obesity phenotype are more susceptible to insulin resistance, what has been confirmed in obese individuals (28).…”
Section: Discussionsupporting
confidence: 65%
“…In addition, studies have shown that high temperature contact can affect insulin hemodynamics, resulting in insulin resistance in the body [29][30].Harmony between biological rhythm and natural rhythm is the basis of normal physiological activities. Irregular shift work will affect the biological rhythm of human body due to irregular circadian rhythm, resulting in the disturbance of nutrients and related hormones in the body, thus resulting in glucose and lipid metabolism disorder and energy imbalance [31].On the other hand, the workers of night shift work lack of sleep time, and the incidence of unhealthy lifestyle such as smoking, drinking and irregular diet increases greatly, which are the driving forces for the occurrence of metabolic syndrome [32].In this study, UA and ALT were found to be risk factors for MetS, and related studies showed that UA increased the risk of MetS by increasing insulin resistance, and increased ALT in the blood might cause fat accumulation in the liver. Through investigation, Mandana Khalili et al found that patients with MetS had higher hepatic steatosis level, and there was a correlation between the elevation of ALT and MetS [33][34].…”
Section: Discussionmentioning
confidence: 99%
“…As an important addendum to the many health consequences of abnormalities of the integrated circadian rhythms, one must just mention disorders in glucose and lipid metabolism as inducers of obesity and the development of Type 2 diabetes [ 53 ] and the multifaceted effects of the circadian control of the immune system and its activation [ 6 , 24 ]. These findings highlight an integrative role of circadian rhythms in physiology [ 7 ].…”
Section: Biological Clocks and Allergic Diseasesmentioning
confidence: 99%